Enhanced luminescence of europium-doped layered double hydroxides intercalated by sensitiser anions. - Gao, X; Hu, M; Lei, L; O'Hare, D; Markland, C; Sun, Y; Faulkner, S (2011)
Four sensitising anions naphthalene-1,5-disulfonate (15-NDS), naphthalene-2,6-dicarboxylate (26-NDC), benzoate (BA) and terephthalate (TA) were intercalated into a Eu(3+)-doped Zn/Al layered double hydroxide. The carboxylate anions enhanced the red luminescence of Eu(3+) much more strongly than the sulfonate, in the descending order TA > 26-NDC > BA > 15-NDS.